Regional differences in vision health: findings from Mwanza, Tanzania. Issue 6 (17th July 2018) - Aggarwal, Sahil; Ju, David; Allen, Angela M; Rose, Laura A; Gill, Karam P; Shen, S Aricia; Temko, Jamie E; Chang, Irene; Faraj, Jessica; Brabender, Danielle E; Herbst de Cortina, Sasha; Marik-Reis, Olivia; et al.
Abstract: Background: Visual impairment in developing countries has both social and economic impact on individuals and communities. Understanding the subjective visual functioning of populations will allow for local policymakers to identify the need for optometric or ophthalmic services in their communities. Methods: The authors surveyed 644 adult patients in Mwanza, Tanzania at three clinics (Buzuruga, Mwananchi and Kisesa) using a modified Visual Functioning Questionnaire 25. Responses were categorized into General health, General vision, Ocular pain, Near activities, Distance activities, Social function, Mental health, Role difficulties, Color vision, Peripheral vision and Dependency. Results: Patients at Buzuruga reported the lowest scores on most subscales. Of 100 employed patients, 37% claimed to have at least some difficulty in performing job duties due to their eyesight. At Kisesa, 146 (246/221) patients (66.1%) had never had an eye exam, compared with 134/227 (59.0%) at Buzuruga and 69/173 (39.9%) at Mwananchi (p<0.01). Common reasons for not seeing an eye doctor were the perceived expense and lack of vision problems. Conclusions: Due to regional differences in visual functioning in Mwanza, a national effort for vision health cannot be entirely successful without addressing the individualized needs of local communities. Reducing the cost of vision care appointments may expand vision health care utilization in Mwanza.